Isoliensinine Suppresses Osteoclast Formation Through NF-κB Signaling Pathways and Relieves Ovariectomy-Induced Bone Loss - Liu, Huijiang; Gu, Ronghe; Huang, Qian; Liu, Yun; Liu, Chong; Liao, Shijie; Feng, Wenyu; Xie, Tianyu; Zhao, Jinmin; Xu, Jiake; Liu, Qian; Zhan, Xinli (Frontiers in Pharmacology, 2022)
Osteoporosis is among the major contributors of pathologic fracture in postmenopausal women, which is caused by the bone metabolic disorder owing to the over-activation of osteoclasts. Inhibition of osteoclast differentiation and maturation has become a mainstream research interest in the prevention of osteoporosis. Isoliensinine (Iso) is a dibenzyl isoquinoline alkaloid with antioxidant, anti-inflammatory, and anti-cancer activities. However, whether it can be used as a potential treatment for osteoporosis remains undiscovered. Here, we investigated whether Iso might suppress the differentiation of osteoclasts in vitro and in vivo to play an anti-osteoporosis role. Our results showed that Iso inhibits the formation of mature multinuclear osteoclasts induced by RANKL, the bone resorption, and the osteoclast-specific genes expression by blocking the nuclear translocation of NF-κB p65, and the effect was in a dosage-dependent way. Furthermore, we investigated the therapeutic effect of Iso on osteoporosis in ovariectomized (OVX) mice. We found that Iso attenuated bone loss in the OVX mice and significantly promoted BS, Conn. DN, Tb.Th, TB.N, and BV/TV Index. All in all, Iso showed a prominent effect of osteoclast inhibition, with great promise for treating osteoporosis.